Amazon Web Services : migrating your .NET Enterprise application : evaluate your Cloud requirements and successfully migrate your .NET Enterprise application to the Amazon Web Services platform /: migrating your .NET Enterprise application : evaluate your Cloud requirements and successfully migrate your .NET Enterprise application to the Amazon Web Services platform. (2011) - Unknown
No abstract available